Thyroid Function at Age Fifty After Prenatal Famine Exposure in the Dutch Famine Birth Cohort - Keestra, Sarai M.; Motoc, Irina; Ravelli, Anita C.J.; Roseboom, Tessa J.; Finken, Martijn J.J. (Frontiers in Endocrinology, 2022)
Background: Early-life exposures during gestation may permanently alter thyroid physiology and health in adulthood. We investigated whether exposure to the Dutch Famine (1944-1945) in late, mid or early gestation influences thyroid function (i.e., incidence of thyroid disease, thyroid autoantibodies, thyroid stimulating hormone (TSH) and free thyroxine (FT4) levels) in adulthood. We specifically assessed whether potential effects of famine differed for men and women. Methods: This study includes 910 men and women born as term singletons in the Wilhelmina Gasthuis in Amsterdam, the Netherlands, shortly before, during, or after the Dutch Famine. We evaluated medical histories for previous diagnosis or current treatment for thyroid dysfunction. At age 50 blood samples were drawn from 728 individuals for tests of thyroid function. We studied the prevalence of overt hypo- and hyperthyroidism and thyroid autoimmunity using medical histories, and measurements of TSH, FT4, anti-TPO and anti-TG, comparing participants exposed to famine at different pregnancy trimesters or born before or conceived after the famine. Additionally, we studied associations of TSH and FT4 levels with in utero famine exposure in a subsample of men and women free of thyroid disease that were exposed in late, mid, or early gestation. Results: There were no differences in thyroid dysfunction diagnosis or current treatment between participants at age 50 years who been exposed to famine during different periods of gestation and those born before or conceived after. There was no association between famine exposure and overt hypo- or hyperthyroidism or thyroid autoantibody positivity. Women who had been exposed to famine in mid gestation had slightly lower TSH levels than women who had not been exposed to famine prenatally (b=-0.06; 95%; CI=[-0.11,-0.02]; p<0.01). No differences in TSH levels were observed in men, and no differences in FT4 levels were observed in men or women. Conclusions: There are no differences in adult thyroid disease at age 50 years according to prenatal famine exposure. However, the lower TSH levels in women exposed to famine in the second trimester suggest that there may be sex-specific effects of famine exposure during a critical period of thyroid development on hypothalamic-pituitary-thyroid axis regulation in adulthood.